Chiến lược marketing trong thư viện và cơ quan thông tin - Nguyễn, Thị Lan Thanh (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Presents basic reasoning problems on marketing strategy in libraries and information institutions, including strategy definition, marketing strategy, mixed marketing strategy and the role of marketing strategy.